The Treatment of HIV by Vibrational Herbal Medicine - Eltouny, Almoez LeDinEllah M. S. (Archives of Clinical and Medical Case Reports, 2019)
The study determines the type of virus, not as a simple but as a set of complex virus system composed of three different complex virus systems. The study also relates how the HIV virus has different energy characteristics not similar to other well known viruses. The energy characteristics of HIV indicate two positive and two negative energy groups. “Normal” viruses,like Hep C, has four negative energy groups. It was finally determined that the cause for the presence of positive and negative energy groups lies in the fact that HIV is composed of three different Major Complex Virus groups and not one monolithic Major Complex Virus like Hep C. All three complex virus systems have to be eliminated to eliminate the HIV virus. Many vibrational herbal mixtures were made over the course of the last 14 years and tried, physically and by simulation, on several patients.The results were mixed until it was discovered that the virus is actually three complex systems in one. Each of the trial mixtures worked on one or two, and not totally fully, on all three systems. The results of our study of the Berlin patient and the Mississippi baby indicate that two of the three viruses were eradicated. Although the main virus in both was the same, the second was different in each, leaving the third virus system untouched. Our latest Vibrational Herbal Mixture eradicates all three complex virus systems, as opposed to the latest chemical experimental treatment which will eliminate the main complex system but will leave the other two, untouched. This may lead to false results as a patient appears to be cured and then the virus reappearing just like the case of the Berlin patient.